A Facile Synthetic Approach toward Obtaining N-Doped Carbon Quantum Dots from Citric Acid and Amino Acids, and Their Application in Selective Detection of Fe(III) Ions - Silvija Šafranko; Kristina Janđel; Monika Kovačević; Anamarija Stanković; Maja Dutour Sikirić; Šimun Mandić; Aleksandar Széchenyi; Ljubica Glavaš Obrovac; Marijana Leventić; Ivica Strelec; Krunoslav Aladić; Stela Jokić (Chemosensors, 2023)
This work reports the preparation of amino acid-functionalized CQDs from citric acid by facile hydrothermal synthesis. The prepared N-doped CQDs exhibited excellent optical, physical, and chemical properties, and the differences were observed among the six different amino acids used as nitrogen dopants (Leu, Trp, Lys, Arg, Ala, His). Compared to the blank sample (without the addition of amino acids), N-doped CQDs have shown significantly higher quantum yield, also demonstrating the potential in metal ion sensing. The highest quantum yield of 36.45%, with a peak excitation/emission of 340/406 nm, was achieved using citric acid and amino acid Leu (CQD@Leu), treated at temperature of 180 °C during 9 h. The prepared samples were investigated toward metal ion selectivity (Ca2+, Cu2+, Fe3+, K+, Hg2+, Mg2+, Al3+, Mn2+, and Na+), and the CQD@Leu showed a selective and sensitive response upon the addition of Fe3+ ions. Therefore, CQD@Leu was selected for further investigation in Fe3+ detection in the model system and real well water samples. A developed model was described by a logistic function with a good coefficient of determination of R2 = 0.9982, while the linear range was determined in the concentration range from 0.3 mol dm−3 to 30 mol dm−3, with a determined limit of detection of LOD = 1.77 ± 0.01 mol dm−3 and limit of quantification of LOQ = 5.89 ± 0.04 mol dm−3. Furthermore, the results of the in vitro cytotoxicity test (MTT) with normal and tumor cell lines (MRC-5, HeLa, NCI-H358, and CaCo-2) clearly demonstrate the excellent biocompatibility of CQD@Leu.